Pengaruh Media Flashcard Dalam Meningkatkan Daya Ingat Siswa Pada Materi Huruf Hijaiyah - Imas Marisa; Hani, Umi; Lies Dharjati (MURABBI, 2022)
Currently, grade I students sometimes find it difficult to understand the learning material. According to the researcher, this is because students at this age have not been confronted directly with real or contextual things. Moreover, seeing the characteristics of 1st grade elementary school children is a concrete operation, which must be faced with something real. The purpose of this study was to determine the effect of flashcard media in improving the memory skills of grade 1 students of SD Islam Terpadu Insan Mulia in learning the Al-Qur'an Hadith material "Huruf Hijaiyah" for the 2022/2023 academic year. The research method used is descriptive quantitative by conducting classroom action research. Data collection techniques were carried out by observation, interviews and documentation. The results of this study indicate that there is an increase in each cycle, starting from the pre-cycle which is only 40%, then increasing in the first cycle as much as 65% and in the second cycle as much as 85%, which means that this flashcard media has an effect on increasing students' memory skills in the hijaiyah letter material. . This is in accordance with research conducted by Titin (2018)